Sustainable Development Strategy for Improving the Competitiveness of Oil Palm Industry - Wisena, Bambang Aria; Daryanto, Arief; Arifin, Bustanul; Oktaviani, Rina (International Research Journal of Business Studies, 2014)
In the Oil World 2014 report, Indonesia is the world’s largest palm oil producer with production of 28 million tons in 2014. Due to increasing market demand for palm oil, environmental and social issues are becoming more essential. This situation requiring a strategy and a policy that is able to balance between the increases of the economic benefits of production while the environmental and social impacts should be minimized. This study aims to identify and describe strategies and policies related to the development of the oil palm industry and its implementation at some companies in Indonesia and to identify factors affecting the competitiveness of the oil palm industry. This study uses ISM (Interpretive Structural Modeling) analytic method with the panel experts of oil palm industry stakeholders from the corporate, government, association, environmental NGOs and academia as respondentts. The results show that the strategy is carried out on the development of a sustainable oil palm industry should increase the attention to the environmental and social aspects with regard to economic aspects. Factors of social, environment, and law enforcement by the government are the most important factors of the strategies.